Variable Learning‐Memory Behavior from π‐Conjugated Ligand to Ligand‐Containing Cobalt(II) Complex†. Issue 19 (26th July 2022) - Zhang, Cheng; Chen, Mohan; Wang, Guan; Teng, Ming; Ling, Songtao; Wang, Yanan; Su, Zhaojun; Gao, Kun; Yang, Xinbo; Ma, Chunlan; Li, Yang; Zhang, Qichun
Comprehensive Summary: In the information‐explosion era, developing novel algorithms and memristive devices has become a promising concept for next‐generation capacity enlargement technology. Organic small molecule‐based devices displaying superior learning‐memory performance have attracted much attention, except for the existence of poor heat‐resilience and mediocre conductivity. In this paper, a strategy of transforming an organic‐type data‐storage material to metal complex is proposed to resolve these intrinsic issues. A pristine NDI‐derivative (NIPy) and its corresponding Co(II) complex (CoNIPy) are synthesized for the purpose of electrical property investigation. CoNIPy complex‐based memristive device exhibits superior ternary WORM memory performance compared with the binary behavior of NIPy, including >10 4 s of reading, lower threshold voltage ( V th ), 1: 10 2 : 10 5 of OFF/ON1/ON2 current ratio, and long‐term stability in heating environment. The variable learning‐memory behavior can be attributed to the enhanced ligand‐to‐metal charge transfer (LMCT) and improved redox activity after the introduction of central metal atom and coordination bond. These studies on material innovation and optimal performance are of great importance not only for environmentally‐robust memristive devices but also for practical application of a host of organic electronic devices. Abstract : To resolve the intrinsic drawback of poor heat‐resilience and mediocre conductivity in organic small molecule‐based memristive devices, a strategy of transforming NDI‐derivative (NIPy) data‐storage material to Co(II) complex is proposed. CoNIPy complex‐based memristive device exhibits superior ternary WORM memory performance compared with the binary property of NIPy, including >10 4 s of reading, lower threshold voltage ( V th ), 1: 10 2 : 10 5 of OFF/ON1/ON2 current ratio, and long‐term stability in heating environment.